Study on the Interaction Between Salvianolic Acid B and Bovine Serum Albumin by Spectroscopic Techniques - Zhu, Qing; Wang, Mei; Liu, Feng; Wang, Xiao (Asian Journal of Chemistry, 2013)
Under simulated physiological conditions, the interaction between salvianolic acid B and bovine serum albumin was investigated using fluorescence spectroscopy, synchronous fluorescence spectroscopy, circular dichroism and ultraviolet spectroscopy at different conditions. As a result, the binding constant (K), the numbers of binding sites (n), the binding distance (r) and the thermodynamic parameters enthalpy change (DHº), the entropy change (DSº), Gibbs free energy change (DGº), are calculated in a simulated human body conditions. The conformation of bovine serum albumin changed in the presence of salvianolic acid B on circular dichroism and synchronous fluorescence spectroscopy. The results show that the static quenching and non-radiative energy transfer lead to the fluorescence quenching of bovine serum albumin and salvianolic acid B-bovine serum albumin system is a spontaneous reaction, the main electrostatic force is hydrophobic effect. In addition, the addition of external common metal ions Cu2+ and K+ decreased the binding constant between salvianolic acid B and bovine serum albumin.